Highly efficient removal of uranium(vi) from wastewater by polyacrylic acid hydrogels. Issue 11 (19th January 2017) - Yi, Xiaofeng; Xu, Zhiqun; Liu, Yan; Guo, Xueyong; Ou, Minrui; Xu, Xiaoping
Abstract : Polyacrylic acid (PAA) hydrogel prepared by radical polymerization in a clean and extremely simple way was used to adsorb U(vi ) ions from aqueous solutions. Abstract : Polyacrylic acid (PAA) hydrogel prepared by radical polymerization in a clean and extremely simple way was used to adsorb U(vi ) ions from aqueous solutions. Fourier transform infrared spectroscopy (FTIR) characterization demonstrated that the PAA hydrogels were successfully synthesized, FTIR and transmission electron microscope (TEM) characterization illustrated the adsorption mechanism, and the adherence of the U(vi ) ions on PAA was confirmed by X-ray photoelectron spectroscopy (XPS) energy dispersive X-ray (EDX). Batch experiments with various pH, initial concentration and contact time were conducted to evaluate the adsorption performance. The adsorption kinetics of the PAA hydrogels followed a pseudo-second-order model and exhibited a 3-stage intraparticle diffusion mode. Equilibrium data were best described by a Langmuir model, and the estimated maximum adsorption capacity for the adsorbent was 445.11 mg g −1 . Moreover, the U(vi ) loaded adsorbent could be regenerated using 0.1 M HNO3 acid solution, and the regenerated adsorbent after five cycles could retain 90.91% of the adsorption capacity of the fresh adsorbent. The results suggested that the PAA hydrogels could be considered to be very effective and promising materials for U(vi ) removal from waste water.